Efficacité des huiles essentielles des plantes sur stadelarvaire L3 de moustique Culex pipiens - Tehatha Khalida (My University, 2022)
This study aims to test the effect of the essential oils of Cinnamomum camphora, Alliumsativum and Urtica dioica to different concentrations on the L3larvas of Culex pipiens in theconditions of the laboratory and according to the recommendations of the world organization ofhealth (WHO).The results show a variable sensitivity of the larvas; this sensitivity is even moreelevated with the increase of the oil concentration. Otherwise, the toxicity is marked well whenthelength ofexhibition of thelarvas is longer.Thecomparison betweenthe: • Three oils (the Cinnamomum camphora, the Allium sativum and the Urtica dioica L)watchthat theoil ofUrtica dioica is themostefficient. • Threeoilsandthemixtureoftwooils(theCinnamomumcamphora+UrticadioicaL),watchthat theoil ofUrtica dioica is themostefficient. • The Three oils and the mixture of the three oils (the Cinnamomum camphora+ theAllium sativum+ the Urtica dioica L), watch that the oil of Urtica dioica is the mostefficient. The toxicological tests done, revealed the activity larvicide of these Oils. Also, the UrticadioicaL oil is moreefficientin relation to theother oils. -------------------------------------------------------------------------------------------------------- تهدف هذه الدراسة إلى اختبار تأثير الزيوت العطرية Cinnamomum camphora و Alliumsativum و Urtica dioica بتراكيز مختلفة على يرقات طائر Culex pipiens في الظروف المخبرية ووفقاً لتوصيات منظمة الصحة العالمية (WHO). حساسية متغيرة لليرقات. وتزداد هذه الحساسية مع زيادة تركيز الزيت. بخلاف ذلك يتم تحديد السمية بشكل جيد عندما يكون طول عرض اليرقات أطول.المقارنة بين: • ثلاثة زيوت (Cinnamomum camphora، وAllium sativum، وUrtica dioica L) تشهد أن زيت Urtica dioica هو الأكثر كفاءة. • ثلاثة زيوت وخليط من زيوت الخشب (القرفة والكامفورا+الأورتيكاديوكال)، شاهد أن زيت الأرتيكا ديويكا هو الأكثر كفاءة. • الزيوت الثلاثة وخليط الزيوت الثلاثة (Cinnamomumcamphora+Allium sativum+Urtica dioica L) تأكد أن زيت Urtica dioica هو الأكثر فعالية. وقد كشفت الاختبارات السمية التي أجريت عن نشاط مبيد اليرقات لهذه الزيوت. كما أن زيت أورتيكاديويكال أكثر كفاءة مقارنة بالزيوت الأخرى. --------------------------------------------------------------------------------------------------------------------- Cetteétudeviseàtesterl’effetdeshuilesessentiellesd’’Cinnamomumcamphora,d’Allium sativum, et d’Urtica dioica L à différentes concentrations sur les larves L3 nouvellementexuviées de Culex pipiens dans les conditions du laboratoire et selon les recommandations del’organisation mondiale de la santé (OMS). Les résultats montrent une sensibilité variable deslarves;cettesensibilitéestencoreplusélevéeavecl'augmentationdelaconcentrationd’huile.Parailleurs, la toxicité est bien marquée lorsque la durée d'exposition des larves est plus longue. Lacomparaisonentreles : • Troishuiles(leCinnamomumcamphora,l’Alliumsativumetl’UrticadioicaL)montrequel’huile d’Urtica dioica est laplus efficace. • Troishuilesetlemélangededeuxhuiles(leCinnamomumcamphora+UrticadioicaL),montrequel’huiled’Urtica dioica est laplus efficace. • Lestroishuilesetlemélangedestroishuiles(leCinnamomumcamphora+l’Alliumsativum+l’UrticadioicaL),montrequel’huiled’Urticadioicaestlaplusefficace. Lesteststoxicologiqueseffectués,ontrévélél’activitélarvicidedecesHuiles.Deplusl’huiled’Urtica dioicaL est plusefficacepar rapportaux autreshuiles.